Study Effectiveness of Some Herbal Extract and Honey on Helicobacter pylori Bacteria: Study Effectiveness of Some Herbal Extract and Honey on Helicobacter pylori Bacteria - Hammadi, Amer A. (Scientific Journal of Medical Research, 2022)
Objectives: The aims of current research detection the inhibition efficiency of alcoholic extraction plants Linum usitatissimium, Gycyrrhiza glabra, Punica granatum and honey each one alone and mixed of these plants with honey to investigate their effectiveness antibacterial action against Helicobacter pylori. Methods: the solvent utilized is ethanol to obtain of cured extract of plants L. usitatissimium, G. glabra, P. granatum extraction and dilution of honey, which tested the effectiveness on H. pylori bacteria to determine the most efficient concentration of solvent optimization, and then was determined minimum inhibitory concentration (MIC) of the extract more efficient. Results: The extraction showed action in vitro against H. pylori comparison with the antibiotic this appear in inhibition zone diameter for these pathogenic bacteria in, G. glabra in concentration (50, 25 mg/mL) (6.23, 1.33 mm) in arreangement and there is effectiveness in treated with honey in (50, 25, 12.5 mg/mL) (13.93, 7.66, 4.03 mm) and mixed of all plants (50, 25, 12.5, 6, and 3 mg/mL) (40.36, 29.23, 18.66, 10.03, 4.56 mm) in diameter. Conclusion: The current research would help isolate new products/drugs. Results of this work have shown that three plant extracts and honey possess compounds with antimicrobial and antioxidant properties.